HIRARC Method for Investigating Worker Behavior Regarding Risk Management - Irfany Rupiwardani; Devita Sari; Tiwi Yuniastuti (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Potential risks and work accidents are things that all sectors of the company must strive to prevent. Construction and production of paving blocks, tiles, and bricks are activities carried out by CV. Pakis Indah, which involves potential production risks. Risk management is needed to control risks in the workplace. The HIRARC approach is used for hazard risk control. This study intends to examine workers' knowledge of occupational health & safety, as well as controlling/reducing the risks. This study uses qualitative and quantitative techniques to calculate risk. Field observations and interviews with six informants were used to obtain data. The findings indicate that there are potential occupational hazards, namely 6 low risks, 9 moderate risks, and 18 high risks. Lack of understanding in the field of K3 results in a lack of awareness of the use of PPE and awareness of work accidents, so that the possibility of danger is not controlled properly. Risk control is carried out by substitution, elimination, administration, mechanical engineering, and the last is personal protective equipment